Implementasi Kebijakan Keterbukaan Informasi Publik di Dinas Komunikasi dan Informatika Kabupaten Tojo Una-Una - Mohammad Rusli Syuaib (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to determine the implementation of public information disclosure policies in the Regional Secretariat of Tojo Una-Una Regency The theory used is the implementation of policies by Van Metter and Van Horn which consists of the size and objectives of the policy, resources, characteristics of implementing agents, attitudes of implementers, communication between organizations and implementing activities, as well as the economic, social and political environment. This type of research is qualitative. The informants of this research are the Regional Secretariat of Tojo Una-Una Regency and observers of public information in Tojo Una-Una Regency which are determined purposively. The data collection and collection techniques consist of observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and drawing conclusions. The results of the study show that it has not fully shown good results because from the aspects studied, there are still three aspects that are not yet supportive, namely in the aspect of resources, characteristics of implementing agents, and communication between implementing organizations. However, the aspect of size and objectives has been carried out in accordance with the policy by forming PPID and preparing SOPs. The attitude of the implementers has shown their support because the implementers are trying to do what is mandated in the policy, while in the economic, social, and political environmental aspects have also shown such a thing where the policy has received support from stakeholders because the policy is a policy that provides opportunities for anyone to obtain public information, including the public. Meanwhile, the resource aspect is still experiencing limitations so that it is difficult to implement policies. The characteristics of the implementing agent are also not good because of the eight sections in the Tojo Una-Una Regency Regional Secretariat, only one part carries out policies in accordance with the public information disclosure policy. Communication between implementing organizations is rarely carried out, so that policy implementers do not understand the content of the policies implemented.